SciVee 2009
DOI: 10.4016/11155.01
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-Unique Domain (SUD) of SARS Coronavirus Contains Two Macrodomains That Bind G-Quadruplexes

Abstract: Since the outbreak of severe acute respiratory syndrome (SARS) in 2003, the three-dimensional structures of several of the replicase/transcriptase components of SARS coronavirus (SARS-CoV), the non-structural proteins (Nsps), have been determined. However, within the large Nsp3 (1922 amino-acid residues), the structure and function of the so-called SARSunique domain (SUD) have remained elusive. SUD occurs only in SARS-CoV and the highly related viruses found in certain bats, but is absent from all other corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…To date, the role of viral macro domains has been demonstrated in the modification of cellular response to viral infection (Nan et al, 2014;Nargi-Aizenman et al, 2002;Tan et al, 2009), as a possible RNA recruitment factor (Malet et al, 2009), or in minus-strand synthesis, P23 processing and/or viral replication (LaStarza et al, 1994a(LaStarza et al, , 1994bLulla et al, 2011). The molecular mechanism or biochemical function behind this role is not well understood.…”
Section: Proteinmentioning
confidence: 97%
“…To date, the role of viral macro domains has been demonstrated in the modification of cellular response to viral infection (Nan et al, 2014;Nargi-Aizenman et al, 2002;Tan et al, 2009), as a possible RNA recruitment factor (Malet et al, 2009), or in minus-strand synthesis, P23 processing and/or viral replication (LaStarza et al, 1994a(LaStarza et al, , 1994bLulla et al, 2011). The molecular mechanism or biochemical function behind this role is not well understood.…”
Section: Proteinmentioning
confidence: 97%
“…Coronaviridae that do not present it (65). Additionally, it has been suggested that the SUD domain interacts with G-quadruplexes of the host.…”
Section: Candidate Confirmation In Vitromentioning
confidence: 99%
“…Macrodomains are found in proteins from all kingdoms of life supporting different cellular processes . Macrodomain‐containing proteins can recognize variety of substrates, including MARylated and PARylated proteins, different ADPr metabolites (such as O AADPr) and RNA (Fig. ).…”
Section: Adpr‐binding Domainsmentioning
confidence: 99%